Space-time structures of earthquakes - T. N. Krishnamurti; Ruby Krishnamurti; Anitha D. Sagadevan; Arindam Chakraborty; William K. Dewar; Carol Anne Clayson; James F. Tull (Meteorology and Atmospheric Physics, 2009)

Predicting future threats to the long-term survival of Gila trout using a high-resolution simulation of climate change - Thomas L. Kennedy; David S. Gutzler; Ruby L. Leung (Climatic Change, 2009)

Nanoscale structures and mechanics of barnacle cement - Ruby May A. Sullan; Nikhil Gunari; Adrienne E. Tanur; Yuri Chan; Gary H. Dickinson; Beatriz Orihuela; Dan Rittschof; Gilbert C. Walker (Biofouling, 2009)

Recognition between symbiotic Vibrio fischeri and the haemocytes of Euprymna scolopes - Spencer V. Nyholm; Jennifer J. Stewart; Edward G. Ruby; Margaret J. McFall‐Ngai (Environmental Microbiology, 2009)
Summary The light organ crypts of the squid Euprymna scolopes permit colonization exclusively by the luminous bacterium Vibrio fischeri. Because the crypt interior remains in contact with seawater, the squid must not only foster the specific symbiosis, but also continue to exclude other bacteria. Investigation of the role of the innate immune system in these processes revealed that macrophage‐like haemocytes isolated from E. scolopes recognized and phagocytosed V. fischeri less than other closely related bacterial species common to the host's environment. Interestingly, phagocytes isolated from hosts that had been cured of their symbionts bound five times more V. fischeri cells than those from uncured hosts. No such change in the ability to bind other species of bacteria was observed, suggesting that the host adapts specifically to V. fischeri . Deletion of the gene encoding OmpU, the major outer membrane protein of V. fischeri , increased binding by haemocytes from uncured animals to the level observed for haemocytes from cured animals. Co‐incubation with wild‐type V. fischeri reduced this binding, suggesting that they produce a factor that complements the mutant's defect. Analyses of the phagocytosis of bound cells by fluorescence‐activated cell sorting indicated that once binding to haemocytes had occurred, V. fischeri cells are phagocytosed as effectively as other bacteria. Thus, discrimination by this component of the squid immune system occurs at the level of haemocyte binding, and this response: (i) is modified by previous exposure to the symbiont and (ii) relies on outer membrane and/or secreted components of the symbionts. These data suggest that regulation of host haemocyte binding by the symbiont may be one of many factors that contribute to specificity in this association.

Non-coding RNAs revealed during identification of genes involved in chicken immune responses - Marie-Laure Endale Ahanda; Thomas Ruby; Håkan Wittzell; Bertrand Bed’Hom; Anne-Marie Chaussé; Veronique Morin; Anne Oudin; Catherine Chevalier; John R. Young; Rima Zoorob (Immunogenetics, 2009)